THE IMPACT OF THE DIGITAL ECONOMY ON ECONOMIC DEVELOPMENT - Dr. Mustafa Kazemi Najaf Abadi, Mohsen Abdulredha Al-Nasiri (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
At the end of the last century, scientific development entered a new stage that traditional society systems transformed into electronic systems through the information and communications technology revolution that drew the features of the new digital economy by relying on the Internet and related equipment such as computers in managing various sectors of society. The digital economy represented the interaction and integration between information and communication technology on the one hand and between the economic sectors of all kinds on the other hand in order to achieve speedy delivery and optimal use of available resources in addition to the quality of goods and services produced which led to transform from an industrial economy based on capital and labor to a digital economy based on modern information technologies and the advantage of abundant production component of research and innovation plays an important role in this era. Iraq has sought to enter the world of information and communication technology in a qualitative manner and to advance an advanced level within international standards to ensure the provision of high-quality services to keep pace with global developments and this requires increased spending in the areas of training and technology education to build the capabilities of individuals and develop and qualify them to manage modern digital institutions, in addition to the possibility of providing a favorable investment climate to help foreign companies invest in technology in the country, which helps to transfer advanced technical and administrative methods in this field.